Digital image correlation based on a fast convolution strategy. (October 2017) - Yuan, Yuan; Zhan, Qin; Xiong, Chunyang; Huang, Jianyong
Highlights: A set of fast convolution-based DIC algorithms are proposed for high-efficiency deformation measurement. A series of global data tables are established to reduce computational complexity of DIC. The set of algorithms are suitable for efficient deformation quantification with high spatial-temporal resolution. Abstract: In recent years, the efficiency of digital image correlation (DIC) methods has attracted increasing attention because of its increasing importance for many engineering applications. Based on the classical affine optical flow (AOF) algorithm and the well-established inverse compositional Gauss–Newton algorithm, which is essentially a natural extension of the AOF algorithm under a nonlinear iterative framework, this paper develops a set of fast convolution-based DIC algorithms for high-efficiency subpixel image registration. Using a well-developed fast convolution technique, the set of algorithms establishes a series of global data tables (GDTs) over the digital images, which allows the reduction of the computational complexity of DIC significantly. Using the pre-calculated GDTs, the subpixel registration calculations can be implemented efficiently in a look-up-table fashion. Both numerical simulation and experimental verification indicate that the set of algorithms significantly enhances the computational efficiency of DIC, especially in the case of a dense data sampling for the digital images. Because the GDTs need to be computed only once, the algorithms are also suitable for efficiently coping with image sequences that record the time-varying dynamics of specimen deformations.